PENGARUH PRAKTIK SUMBER DAYA MANUSIA TERHADAP PERILAKU KEWARGANEGARAAN ORGANISASI - Basuki Basuki; Rahmi Widyanti; Farida Yulianti; Lamsah Lamsah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The relationship between human resource management and organizational performanceis very important to understand. Good human resource practices within the company canincrease the good behavior of members of the organization.This study aims to determine how practices in human resources affect organizationalcitizenship behavior (OCB). OCB represents the additional contribution of the employee tothe company and, however, the actions that the employee expects in a crisis scenario or achange in timing by the manager. In this study, it uses five main indicators in humanresource management practices in organizations according to the HR field: recruitment andselection, training and development, remuneration, performance appraisal, and workingconditions. Organizational Citizenship Behavior Scale (SPKO), which contains fivedimensions: disclosure of organizational image; creative suggestions; protection oforganizational assets; professional preparation and cooperation with colleagues. Data werecollected from 56 employees of wood processing companies located in Banjarmasin City.Data analysis used Partial Least Square (PLS) with SmartPLS software.The results show a significant effect of human resource practices on OCB, and thisstudy proves that only professional involvement shows a significant relationship. This studyconcludes that human resource practices influence the dissemination of organizationalimages and creative suggestions from the OCB factor.